Unlocking the potential of geological storage of CO2: what role for a Storage Climate Club? - Al Juaied, Mohammed; Carey, Elizabeth (Frontiers in Sustainable Energy Policy, 2025)
Carbon Capture and Storage (CCS) is a key carbon dioxide (CO2) mitigation technology in climate change mitigation pathways that aim to limit the rise in temperatures to below 1. 5 and 2 °C, in line with the recommendations of the Intergovernmental Panel on Climate Change (IPCC). This policy brief focuses on the deployment at scale of geological storage of CO2 as the last critical link in the CCS process chain. It proposes the establishment of a new Storage Climate Club led by a group of “enthusiastic” countries in order to operationalize a new asset class, Carbon Storage Units (CSUs) under Article 6 of the Paris Agreement and support the deployment at scale of geological storage of CO2 and CCS technologies worldwide.